Perinatal Chicken Pox (Varicella Zoster Virus) Infection - Ali Annagur; Ayhan Tastekin; Pervin Gunaslan; Oguzhan Demirel; Ahmet Hakan Dikener (Çukurova Üniversitesi Tıp Fakültesi Dergisi)
Chickenpox is due to infection with the varicella zoster virus (VZV), a human alphaherpervirus found worldwide. Classically, the cinical disease is a febrile illness with a pruritic vesicular rash. Maternal chickenpox between 5 days before delivery to 2 days after delivery (perinatal varicella) can cause severe and even fatal illness in the newborn. A 7-day old girl baby presented on day 4 of postnatal with the complaints of widespread vesicular rash and non-suckling. Mother of the baby also had a similar eruption four day prior to delivery, which was clinically characteristic of varicella. Considering history and clinical presentation, a diagnosis of perinatal chickenpox was considered and the baby was treated with acyclovir which she responded and recovered. Herein, the clinical feasures and treatment of chickenpox infection in the perinatal period have been emphasized with this case report. [Cukurova Med J 2013; 38(2.000): 311-314]